2013
DOI: 10.1091/mbc.e13-03-0121
|View full text |Cite
|
Sign up to set email alerts
|

Deacylation on the matrix side of the mitochondrial inner membrane regulates cardiolipin remodeling

Abstract: Our understanding of the clinically relevant tafazzin-mediated cardiolipin (CL) remodeling pathway is incomplete. In this study, a new trafficking step required for CL remodeling has been identified. Further, it is demonstrated that flux through this CL remodeling pathway is controlled by the strength of the mitochondrial electrochemical gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 98 publications
3
57
0
Order By: Relevance
“…Thus, CL remodeling may require the coordinated action of phospholipase(s) and transacylase(s), such as tafazzin. Nevertheless, because tafazzin and Cld1 (both contain no transmembrane segment) are associated with the intermembrane space-facing and matrix-facing leaflets of the mitochondrial inner membrane, respectively (4,45), MLCL generated by Cld1 must be transported to the intermembrane space-facing leaflet to gain access to tafazzin, suggesting the existence of an as yet unidentified protein(s) capable of redistributing MLCL across the inner membrane. Further studies are needed to establish all of the involved players and elucidate their roles in CL remodeling in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CL remodeling may require the coordinated action of phospholipase(s) and transacylase(s), such as tafazzin. Nevertheless, because tafazzin and Cld1 (both contain no transmembrane segment) are associated with the intermembrane space-facing and matrix-facing leaflets of the mitochondrial inner membrane, respectively (4,45), MLCL generated by Cld1 must be transported to the intermembrane space-facing leaflet to gain access to tafazzin, suggesting the existence of an as yet unidentified protein(s) capable of redistributing MLCL across the inner membrane. Further studies are needed to establish all of the involved players and elucidate their roles in CL remodeling in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Although different approaches have been used, this proposed model is similar to the model described in Baile et al (39), in which they suggested a feedback loop between oxidative phosphorylation and CL remodeling. Specifically, they found that CLD1 expression is regulated by carbon sources, and the activity of Cld1 is increased by dissipating the mitochondrial membrane potential (39). They suggested that CL remodeling functions to increase oxidative phosphorylation efficiency and/or replace oxidized CL.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Following the de novo synthesis of CL on the matrix side of the inner mitochondrial membrane, CL undergoes remodeling in which acyl chains are exchanged. In this process, CL is deacylated to monolysocardiolipin (MLCL) by the CL-specific lipase Cld1 on the matrix side of the inner mitochondrial membrane (38,39). MLCL is reacylated by the transacylase Taz1 in the mitochondrial periphery (40 -43).…”
Section: Cardiolipin (Cl)mentioning
confidence: 99%
“…69 The presence of non-linoleic acyls disrupts the compact configuration of (C18:2) 4 -CL, paradoxically increasing the oxidative sensitivity of the asymmetric CL. 20 ALCAT1 is located in the endoplasmic reticulum, 70 suggesting that secondary CL remodeling may require mitochondria-endoplasmic reticulum interactions. Since secondary remodeling of CL by ALCAT1 is extramitochondrial, it is unlikely that regional defects would be present.…”
Section: Mitochondrial Morphology In the Aging Heartmentioning
confidence: 99%